2007
DOI: 10.2110/palo.2005.p05-121r
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Atlantic Sturgeon Feeding Excavations, Mary's Point, Bay of Fundy, New Brunswick, Canada

Abstract: In this study we report on the occurrence and potential significance of Atlantic sturgeon (Acipenser oxyrhynchus) feeding traces observed in the Bay of Fundy in great abundance on the intertidal mud flats of Mary's Point, New Brunswick, Canada. The traces comprise a crescent-shaped impression and a plug-shaped excavation and are considered to be a modern analogue for the trace fossil Piscichnus. Local areas exhibit relatively great numbers of the feeding structure: the sediment in these zones contains bivalves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…In fact, Rochard et al (2001) indicated that although these high-occupancy areas looked similar in terms of depth and bottom type to areas with reduced occupancy, it was believed that it may be due to these having lower flows and finer sediments which may develop different benthic resources (Wooley & Crateau 1985, Carr et al 1996. Finally, Pearson et al (2007) noted sediment excavations made by feeding Atlantic sturgeon in the Bay of Fundy, Canada, near shore mud flats which coincided spatially with high density areas of amphipods, bivalves, and nereid polychaetes; the greatest number of feeding excavations were in areas with the greatest density of amphipods (within 500 m of mean high tide). McLean et al (2013) recently quantified that 21 sub-adult and adult Atlantic sturgeon consumed mainly tube-dwelling polychaetes (Maldanidae and Spionidae) in sandy, estuarine intertidal mudflats of Minas Basin, Canada.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, Rochard et al (2001) indicated that although these high-occupancy areas looked similar in terms of depth and bottom type to areas with reduced occupancy, it was believed that it may be due to these having lower flows and finer sediments which may develop different benthic resources (Wooley & Crateau 1985, Carr et al 1996. Finally, Pearson et al (2007) noted sediment excavations made by feeding Atlantic sturgeon in the Bay of Fundy, Canada, near shore mud flats which coincided spatially with high density areas of amphipods, bivalves, and nereid polychaetes; the greatest number of feeding excavations were in areas with the greatest density of amphipods (within 500 m of mean high tide). McLean et al (2013) recently quantified that 21 sub-adult and adult Atlantic sturgeon consumed mainly tube-dwelling polychaetes (Maldanidae and Spionidae) in sandy, estuarine intertidal mudflats of Minas Basin, Canada.…”
Section: Discussionmentioning
confidence: 98%
“…Actualistic studies provide the data that make trace fossils invaluable to paleoecological and paleoenvironmental reconstructions. There are numerous examples of these types of studies with marine animals (Frey, 1968(Frey, , 1970Ekdale and Berger, 1978;Gregory et al, 1979;Frey et al, 1984;Pemberton and Frey, 1985;Frey et al, 1987;Gaillard, 1991;Kanazawa, 1992;Alexander et al, 1993;Seilacher and Seilacher, 1994;Gingras et al, 2002Gingras et al, , 2004Curran and Martin, 2003;De, 2005;Needham et al, 2005;Martin, 2006;Uchman and Pervesler, 2006;Hertweck et al, 2007;Pearson et al, 2007;Seike and Nara, 2007;Dashtgard et al, 2008), but fewer studies have involved terrestrial burrowing animals (Ahlbrandt et al, 1978;Ratcliffe and Fagerstrom, 1980;Hasiotis and Mitchell, 1993;O'Geen and Busacca, 2001;Deocampo, 2002;Tschinkel, 2003;Gobetz, 2005;Hasiotis, 2006, 2007;Lawfield and Pickerill, 2006;Davis et al, 2007;Gingras et al, 2007;Rodríguez-Tovar, 2007;Scott et al, 2007;Smith and Hasiotis, 2008;Counts and Hasiotis, 2009). The purpose of this type of research is to study modern continental burrowing organisms in order to determine their trace-making behaviors and resulting architectural and surficial burrow morphologies (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Larger structures, some of which are similar conceptually to Piscichnus, have been reported as animal bite marks out of the sediment. These are centimeter-to-meter scale and take on a host of morphologies , Pearson et al, 2007.…”
Section: Introductionmentioning
confidence: 99%